A qualitative study of attitudes towards suicide and suicide prevention among psychology students in Ghana - Knizek, B.L.; Akotia, C.S.; Hjelmeland, H. (Baywood Publishing Co., Inc., 2010)
The purpose of the present study was to investigate attitudes toward suicide and suicide prevention among psychology students in Ghana by means of a qualitative analysis of open-ended questions about causes of suicide and how suicide best can be prevented. The students mainly saw the causes as intra-personal and almost all of them believed that suicide can be prevented. The results indicated a huge impact of religion on the attitudes toward suicide as well as some lack of distinction between their religious and professional roles and responsibilities.